Spectral Characterization of Bennu Analogs Using PASCALE: A New Experimental Set‐Up for Simulating the Near‐Surface Conditions of Airless Bodies. Issue 2 (18th February 2021) - Donaldson Hanna, K. L.; Bowles, N. E.; Warren, T. J.; Hamilton, V. E.; Schrader, D. L.; McCoy, T. J.; Temple, J.; Clack, A.; Calcutt, S.; Lauretta, D. S.
Abstract: We describe the capabilities, radiometric stability, and calibration of a custom vacuum environment chamber capable of simulating the near‐surface conditions of airless bodies. Here we demonstrate the collection of spectral measurements of a suite of fine particulate asteroid analogs made using the Planetary Analogue Surface Chamber for Asteroid and Lunar Environments (PASCALE) under conditions like those found on Earth and on airless bodies. The sample suite includes anhydrous and hydrated physical mixtures, and chondritic meteorites (CM, CI, CV, CR, and L5) previously characterized under Earth‐ and asteroid‐like conditions. And for the first time, we measure the terrestrial and extra‐terrestrial mineral end members used in the olivine‐ and phyllosilicate‐dominated physical mixtures under the same conditions as the mixtures and meteorites allowing us better understand how minerals combine spectrally when mixed intimately. Our measurements highlight the sensitivity of thermal infrared emissivity spectra to small amounts of low albedo materials and the composition of the sample materials. As the albedo of the sample decreases, we observe smaller differences between Earth‐ and asteroid‐like spectra, which results from a reduced thermal gradient in the upper hundreds of microns in the sample. These spectral measurements can be compared to thermal infrared emissivity spectra of asteroid (101955) Bennu's surface in regions where similarly fine particulate materials may be observed to infer surface compositions. Plain Language Summary: In this work, we measure fine particulate terrestrial and extra‐terrestrial minerals, physical mixtures made from those minerals, and meteorites using a bespoke environment chamber at the University of Oxford. We selected minerals that were similar in composition to those found in carbonaceous chondrites and physical mixtures were made to simulate the composition of anhydrous and hydrated carbonaceous chondrites. Thermal infrared emissivity spectra were collected under Earth‐ and Bennu‐like conditions using a vacuum chamber capable of simulating the near‐surface conditions of planetary bodies with no appreciable atmosphere. These spectra are invaluable for to interpreting current and future observations of primitive Solar System bodies, particularly those with fine particulate regoliths. Key Points: Thermal infrared spectra of fine particulate minerals, physical mixtures of those minerals, and meteorites were measured under simulated Bennu conditions Comparisons of mineral, physical mixture, and meteorite spectra highlight the spectral behavior when materials are mixed in increasing complexity As albedo decreases the spectral effects due to thermal gradients due to the vacuum environment of airless bodies are reduced